Design Verification of a Hybrid Wave-Damping System for Sustainable and Multi-Hazard-Resilient Port Infrastructure at Merak Port (Berth VII), Indonesia - Suwanto Marsudi; Rahmah Dara Lufira; Ussy Andawayanti; Ery Suhartanto; M.Amar Sajali; Rizki Tri Utami (Jurnal Penelitian Pendidikan IPA, 2026)
Merak Port Berth VII is exposed to wave action, seismic loading, and soft-soil conditions, while retrofit works must be planned under limited marine access and a constrained schedule. This study verifies a hybrid wave-damping system comprising a platform-mounted wavescreen and a causeway revetment to improve multi-hazard resilience. Wind data from 2010–2022 were used for wave hindcasting to derive return-period wave conditions, while seismic actions and structural checks were evaluated using Indonesian and international port design criteria. Platform performance was assessed at the ultimate and serviceability limit states, and revetment stability was analyzed using the Morgenstern–Price method. Under the 500-year design combination, the platform satisfied strength and serviceability requirements, with vertical bearing safety factors of 3.40 and 3.53 based on SNI and UFC combinations, respectively, and deformations within operational limits. The revetment achieved a factor of safety of 1.49 under the same demand but became inadequate under the 1,000-year scenario, indicating the need for strengthening when higher reliability is required. The estimated construction cost is IDR 132,205,000,000, with an estimated duration of approximately 216 working days. This verification framework is transferable to brownfield Indonesian ports exposed to combined coastal and seismic hazards.